A titanium oxide film catalytic material for rapid and high-yield synthesis of imines, and preparation method and use thereof
By developing titanium oxide film catalytic materials with continuous adjustable layer spacing and titanium-oxygen atom ratio, the existing photocatalytic reaction time and low yield are solved by using the two-dimensional nano-domain confined channels and photoexcited reactive oxygen species synergistic catalytics. The problem is that the imine synthesis with rapid and high yield is achieved, which is in line with the concept of green chemistry.
Patent Information
- Application Number
- CN202411622792.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The existing photocatalytic reaction based on titanium dioxide has problems such as long reaction time, low yield, oxygen atmosphere or heating, and large catalyst usage, and does not conform to the concept of green chemistry.
Develop a titanium oxide film catalytic material with continuously adjustable layer spacing and titanium oxygen atomic ratio, synergistic catalytic effects of two-dimensional nano-domain confined channels provided between membrane layers by titanium oxide nanosheets and photoexcited reactive oxygen species , achieve rapid and high yield photocatalytic synthesis of imine.
The photocatalytic synthesis of imines with rapid and high yields (0.1-100s, 70-100%) is achieved, which simplifies the separation and purification process and reduces the dependence on oxygen and heat sources, which is in line with the concept of green chemistry.
Smart Images

Figure CN119140080B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a titanium oxide film catalytic material with adjustable interlayer spacing, adjustable thickness and adjustable excitation light intensity, a preparation method thereof and application in photocatalytic preparation of imines, belonging to the field of film catalytic materials and technology. Background Art
[0002] Imines are important intermediates in the pharmaceutical, agricultural, and synthetic fields, and can be further used in the synthesis of quinolones, cucurbiturils, and oxazaheterocycles. Their general formula is R1C=NR2, and they are organic compounds formed when the oxygen atom on the carbonyl group is replaced by nitrogen. The typical method for preparing imines is through the condensation reaction of a primary amine and an aldehyde. The reaction mechanism involves the amine's lone pair of electrons initially attacking the carbonyl group, resulting in a nucleophilic addition reaction to form a hemiaminal (-C(OH)(NHR)-) intermediate. This reaction then proceeds to eliminate a water molecule to yield the imine. However, because the reaction equilibrium favors the carbonyl compound and the amine, azeotropic distillation, reflux separation, or the use of a dehydrating agent (such as molecular sieves or concentrated sulfuric acid) is required to shift the equilibrium toward the formation of the imine.
[0003] The photocatalytic coupling of benzylamines to imines offers a new technological path for the preparation of imines. Titanium dioxide (such as commercially available P25), a typical photocatalyst, is widely used in various fields, including food, medicine, and cosmetics. Under light irradiation, electrons and holes in titanium dioxide separate, forming reactive oxygen species that promote the coupling of benzylamines. However, current titanium dioxide-based photocatalytic reactions suffer from long reaction times (>6 hours), low yields (<49%), the requirement for an oxygen atmosphere (>1 atm oxygen) or heating (>60°C), and high catalyst requirements. These reactions, while consuming significant amounts of reagents and time, also pose significant environmental risks, contradicting the principles of green chemistry. Summary of the Invention
[0004] To address the shortcomings of existing technologies in achieving rapid and high-yield imine synthesis, the present invention provides a titanium oxide film catalytic material for photocatalytic imine synthesis, as well as its preparation method and use. The titanium oxide film catalytic material has a continuously adjustable interlayer spacing while retaining the titanium oxide nanosheet structure. Through the synergistic catalytic effect of the two-dimensional nanoconfined channels provided by the titanium oxide nanosheets between the film layers and the photoexcited reactive oxygen species, rapid and high-yield catalytic imine synthesis is achieved. Furthermore, the imine synthesis is accomplished using a continuous mobile phase reaction, with the product escaping with the mobile phase and exiting the system, simplifying the separation and purification process.
[0005] The object of the present invention is achieved through the following technical solutions:
[0006] A titanium oxide film catalytic material has an interlayer spacing of 1.40 nm to 1.60 nm and an atomic ratio of titanium to oxygen of 0.440 to 0.465.
[0007] According to an embodiment of the present invention, the titanium oxide film catalytic material has the characteristic of semiconductor properties with continuously adjustable interlayer spacing.
[0008] According to an embodiment of the present invention, the titanium oxide film catalytic material is a titanium oxide film confined catalytic material, which provides an ordered two-dimensional confined channel for the reactants. The interlayer spacing of the titanium oxide film catalytic material is adjustable, and the atomic ratio of titanium and oxygen in the titanium oxide film catalytic material is adjustable; the adjustment of the interlayer spacing can affect the size of the two-dimensional nano-confined channel, the adjustment of the titanium-oxygen atomic ratio can affect the amount of photoexcited active oxygen species, and the adjustment of the synergistic catalytic effect of the two-dimensional nano-confined channel and the active oxygen species can optimize the catalytic performance of the titanium oxide film catalytic material.
[0009] According to an embodiment of the present invention, the interlayer spacing of the titanium oxide film catalytic material is 1.40 nm, 1.42 nm, 1.45 nm, 1.48 nm, 1.50 nm, 1.52 nm, 1.55 nm, 1.58 nm, or 1.60 nm. Research has found that the interlayer spacing can be controlled by regulating the heat treatment temperature; the higher the heat treatment temperature, the smaller the interlayer spacing.
[0010] According to an embodiment of the present invention, the atomic ratio of titanium to oxygen in the titanium oxide film catalyst material is 0.440, 0.445, 0.450, 0.455, 0.460, or 0.465. Research has found that the atomic ratio of titanium to oxygen can be adjusted by adjusting the mixing ratio of titanium dioxide and cesium carbonate, the raw materials used to prepare the titanium oxide film catalyst material.
[0011] According to an embodiment of the present invention, the thickness of the titanium oxide film catalytic material is 0.5-10 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm. By adjusting the film thickness, the retention time of the reacting molecules within the two-dimensional nanoconfined channels of the titanium oxide film catalytic material can be controlled, thereby optimizing its catalytic performance. Studies have found that titanium oxide film catalytic materials that are too thin (thickness less than 0.5 μm) have poor mechanical properties and are prone to failure during subsequent catalytic reactions. Titanium oxide film catalytic materials that are too thick (thickness greater than 10 μm) are prone to introducing excessive defects, reducing the structural order of the two-dimensional nanoconfined channels provided for the reacting molecules. In addition, titanium oxide film catalytic materials that are too thick (thickness greater than 10 μm) are not easily penetrated by ultraviolet light, and cannot excite the titanium oxide nanosheets above and below the two-dimensional nanoconfined channels to carry out photocatalytic reactions.
[0012] The present invention also provides a method for preparing the above titanium oxide film catalytic material, and the method comprises the following steps:
[0013] (1) Mix titanium dioxide and cesium carbonate, and calcine to prepare cesium titanate in a layered structure; mix the layered cesium titanate with an acid to carry out a protonation reaction to prepare titanic acid;
[0014] (2) Add titanic acid to an aqueous solution of tetrabutylammonium hydroxide to carry out a delamination reaction to prepare titanium oxide nanosheets;
[0015] (3) Assemble the titanium oxide nanosheets into a titanium oxide film by vacuum filtration to prepare the titanium oxide film catalytic material.
[0016] According to an embodiment of the present invention, in step (1), the titanium dioxide is preferably nano-titanium dioxide, for example, nano-titanium dioxide with a particle size of 20-40 nm is selected.
[0017] According to an embodiment of the present invention, in step (1), the source of the titanium dioxide is not particularly defined, and it can be prepared by a method known in the art or obtained by purchasing through commercial channels.
[0018] According to an embodiment of the present invention, in step (1), the mass ratio of the titanium dioxide to the cesium carbonate is 1:0.5-3, for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.5, 1:2.0, 1:2.5 or 1:3.0. By adjusting the mass ratio of the titanium dioxide to the cesium carbonate, cesium titanate (Cs x Ti 2-x / 4 O4, 0.6 < x ≤ 1.0) with different compositions can be obtained for preparing titanium oxide film catalytic materials with different atomic ratios of titanium to oxygen; meanwhile, the particle size and crystallinity of the cesium titanate can also be adjusted, so as to obtain a titanium oxide film catalytic material with photocatalytic activity.
[0019] According to an embodiment of the present invention, in step (1), the temperature of the calcination is 600 - 1000 °C, for example, 600 °C, 650 °C, 700 °C, 750 °C, 800 °C, 850 °C, 900 °C, 950 °C or 1000 °C; the time of the calcination is 10 - 40 hours, for example, 10 hours, 12 hours, 15 hours, 16 hours, 20 hours, 24 hours, 30 hours, 36 hours or 40 hours; the heating rate of the calcination is 2 - 10 °C / min, for example, 2 °C / min, 3 °C / min, 5 °C / min, 6 °C / min, 8 °C / min or 10 °C / min; the cooling rate of the calcination is 2 - 10 °C / min, for example, 2 °C / min, 3 °C / min, 5 °C / min, 6 °C / min, 8 °C / min or 10 °C / min; the calcination is carried out in an air atmosphere.
[0020] According to an embodiment of the present invention, in step (1), the number of times of the calcination is 1 - 3 times, for example, 2 times; repeating the calcination multiple times can make the raw materials mix more fully and obtain cesium titanate with higher purity; preferably, after the first calcination ends, the temperature of the calcination product is cooled to room temperature and then ground, and then the second calcination is carried out.
[0021] According to an embodiment of the present invention, in step (1), the chemical formula of the titanium dioxide is TiO2.
[0022] According to an embodiment of the present invention, in step (1), the chemical formula of the cesium carbonate is Cs2CO3.
[0023] According to an embodiment of the present invention, in step (1), the chemical formula of the cesium titanate is Cs x Ti 2-x / 4 O4, 0.6 < x ≤ 1.0; exemplarily, the chemical formula of the cesium titanate is Cs 0.7 Ti 1.825 O4.
[0024] According to an embodiment of the present invention, in step (1), the chemical formula of the titanic acid is H x Ti 2-x / 4 O4, 0.6 < x ≤ 1.0; exemplarily, the chemical formula of the titanic acid is H 0.7 Ti 1.825 O4.
[0025] According to an embodiment of the present invention, in step (1), the acid is an inorganic strong acid, such as hydrochloric acid or sulfuric acid; the concentration of the acid is 0.1-3.0 mol / L, such as 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L or 3.0 mol / L.
[0026] According to an embodiment of the present invention, in step (1), the protonation reaction time is 24-96 hours, for example, 48 hours or 72 hours; and the protonation reaction temperature is room temperature.
[0027] According to an embodiment of the present invention, in step (2), the concentration of the aqueous solution of tetrabutylammonium hydroxide is 0.001-0.1 mol / L, for example, 0.001 mol / L, 0.002 mol / L, 0.003 mol / L, 0.004 mol / L, 0.005 mol / L, 0.006 mol / L, 0.007 mol / L, 0.008 mol / L, 0.009 mol / L, 0.01 mol / L or 0.1 mol / L.
[0028] According to an embodiment of the present invention, in step (2), the time of the stripping reaction is 3-21 days, for example, 7 days or 14 days; the temperature of the stripping reaction is room temperature.
[0029] According to an embodiment of the present invention, in step (2), the stripping reaction is carried out under shaking conditions.
[0030] According to an embodiment of the present invention, in step (2), the mass molar ratio of titanic acid and tetrabutylammonium hydroxide is 0.05-1 g / mmol, for example, 0.05 g / mmol, 0.1 g / mmol, 0.15 g / mmol, 0.2 g / mmol, 0.3 g / mmol, 0.4 g / mmol, 0.5 g / mmol, 0.6 g / mmol, 0.7 g / mmol, 0.8 g / mmol, 0.9 g / mmol or 1 g / mmol.
[0031] According to an embodiment of the present invention, in step (2), the titanium oxide nanosheets are preferably single-layer titanium oxide nanosheets.
[0032] According to an embodiment of the present invention, in step (2), the thickness of the titanium oxide nanosheets is 1.0 nm-1.5 nm, for example, 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm or 1.5 nm.
[0033] According to an embodiment of the present invention, in step (2), the chemical formula of the titanium oxide nanosheet is Ti y O2, 0.93≥y≥0.88; For example, the chemical formula of the titanium oxide nanosheet is Ti 0.91 O2.
[0034] According to an embodiment of the present invention, in step (3), the thickness of the titanium oxide film catalytic material is 0.5-10 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0035] According to an embodiment of the present invention, step (3) specifically includes the following steps:
[0036] (3-1) Preparing a titanium oxide nanosheet dispersion;
[0037] (3-2) The titanium oxide nanosheet dispersion of step (3-1) is assembled into a titanium oxide film by vacuum filtration, and then subjected to a constant temperature and humidity static treatment to prepare the titanium oxide film catalytic material.
[0038] According to an embodiment of the present invention, in step (3-1), the concentration of titanium oxide in the titanium oxide dispersion is 0.1-5 mg / mL, for example, 0.1 mg / mL, 0.25 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL or 5 mg / mL.
[0039] According to an embodiment of the present invention, in step (3-1), the titanium oxide dispersion contains titanium oxide nanosheets, tetrabutylammonium hydroxide and deionized water.
[0040] According to an embodiment of the present invention, in step (3-2), the titanium oxide film catalytic material is a layered structure formed by stacking titanium oxide nanosheets.
[0041] According to an embodiment of the present invention, in step (3-2), the titanium oxide dispersion of step (3-1) is added to a filter cup provided with a vacuum filtration device, and the vacuum pump is started to perform vacuum filtration with a vacuum degree of 1-5 Pa.
[0042] According to an embodiment of the present invention, a porous substrate is laid in the filter cup, that is, a membrane formed by stacking multiple single-layer titanium oxide nanosheets of a certain thickness is prepared on the porous substrate by vacuum filtration.
[0043] The porous substrate may be made of an organic filter membrane such as nylon 66, polyvinylidene fluoride, or polytetrafluoroethylene.
[0044] The pore size of the porous substrate is 0.1-0.3 μm, for example, 0.22 μm.
[0045] According to an embodiment of the present invention, in step (3-2), as the filtration proceeds, the titanium oxide nanosheets in the titanium oxide dispersion are assembled into a layered structure under the action of water flow, and when the filtration is completed, the titanium oxide film catalytic material is obtained.
[0046] According to an embodiment of the present invention, in step (3-2), the constant temperature and humidity static treatment is, for example, performed under constant temperature and humidity conditions for a period of time, such as in a constant temperature and humidity chamber. Exemplarily, the static treatment is performed at 20-25°C and 5-20% RH for 2-12 hours.
[0047] According to an embodiment of the present invention, in step (3-2), the constant temperature and humidity static treatment can achieve the removal of free water in the titanium oxide film after the filtration is completed.
[0048] According to an embodiment of the present invention, the method further comprises the following steps:
[0049] (4) Heat-treating the titanium oxide film catalytic material of step (3).
[0050] According to an embodiment of the present invention, in step (4), the heat treatment time is 8-16 hours, for example, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours or 16 hours; the heat treatment temperature is 40-120°C, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C. A heat treatment temperature that is too low (<40°C) is not conducive to water loss and cannot effectively control the interlayer spacing of the titanium oxide film catalyst material; a heat treatment temperature that is too high (>120°C) will denature titanium oxide, which is not conducive to maintaining the intrinsic chemical structure of the titanium oxide film catalyst material, and will also increase the mass transfer resistance of the titanium oxide film catalyst material, affecting the mobility of the reactant molecules.
[0051] According to an embodiment of the present invention, in step (4), the heat treatment is performed in a vacuum oven.
[0052] According to an embodiment of the present invention, in step (4), the heat treatment can remove part of the bound water present between the layers of the titanium oxide film catalyst material, which can effectively regulate the interlayer spacing of the titanium oxide film catalyst material and obtain a titanium oxide film catalyst material with continuously adjustable interlayer spacing.
[0053] The present invention also provides a titanium oxide film catalytic material prepared by the above method.
[0054] The present invention also provides a use of the titanium oxide film catalytic material, which is used for photocatalytic coupling of benzylamine compounds to prepare imines.
[0055] According to an embodiment of the present invention, the titanium oxide film catalytic material is used for rapid photocatalytic coupling of benzylamine compounds to prepare imines.
[0056] According to an embodiment of the present invention, the titanium oxide film catalytic material is used for rapid and high-yield photocatalytic coupling of benzylamine compounds to prepare imines.
[0057] According to an embodiment of the present invention, the rapid reaction time refers to a reaction time range of 0.1-100s, for example, 0.1s, 0.2s, 0.3s, 0.4s, 0.5s, 0.6s, 0.7s, 0.8s, 0.9s, 1s, 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s or 100s.
[0058] According to an embodiment of the present invention, the high yield refers to a reaction yield range of 70-100%, for example, 70%, 75%, 80%, 85%, 90%, 95% or 100%.
[0059] According to an embodiment of the present invention, the coupling of benzylamine compounds to prepare imines is carried out in a continuous mobile phase reaction under ultraviolet light irradiation and driven by pressure difference. The benzylamine compounds react in the two-dimensional nano-confined channel of the titanium oxide film catalytic material, and the product imine flows out with the mobile phase and leaves the system.
[0060] The present invention also provides a method for preparing imines by photocatalytic coupling of benzylamine compounds, the method comprising the following steps:
[0061] (1) dissolving the benzylamine compound in an organic solvent to obtain a transmembrane reaction solution;
[0062] (2) Driven by pressure difference, the cross-membrane reaction solution is irradiated by ultraviolet light and passes through the above-mentioned titanium oxide film catalyst material to carry out a photocatalytic benzylamine compound coupling reaction.
[0063] According to an embodiment of the present invention, in step (1), the concentration of the benzylamine compound in the transmembrane reaction solution is 0.01-5 mol / L, for example, 0.01 mol / L, 0.02 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L or 5 mol / L.
[0064] According to an embodiment of the present invention, in step (1), the organic solvent is a polar solvent, such as acetonitrile.
[0065] According to an embodiment of the present invention, in step (1), the benzylamine compound is selected from benzylamine and its ortho-, meta- and para-substituted homologues; illustratively, the benzylamine compound is selected from at least one of benzylamine, 2-methylbenzylamine, 3-methylbenzylamine, 4-methylbenzylamine, 2-trifluoromethylbenzylamine, 3-trifluoromethylbenzylamine, 4-trifluoromethylbenzylamine, 2-methoxybenzylamine, 3-methoxybenzylamine, 4-methoxybenzylamine, 2-tert-butylbenzylamine, 3-tert-butylbenzylamine, 4-tert-butylbenzylamine, 2,3-difluorobenzylamine, 2,4-difluorobenzylamine, 2,3-dichlorobenzylamine, 2,4-dichlorobenzylamine, 2,3-dibromobenzylamine, 2,4-dibromobenzylamine, 2-fluorobenzylamine, 3-fluorobenzylamine, 4-fluorobenzylamine, 2-chlorobenzylamine, 3-chlorobenzylamine, 4-chlorobenzylamine, 2-bromobenzylamine, 3-bromobenzylamine and 4-bromobenzylamine.
[0066] According to an embodiment of the present invention, in step (2), the reaction time is 0.1-100s.
[0067] According to an embodiment of the present invention, in step (2), no additional heat source needs to be introduced during the photocatalytic coupling reaction of the benzylamine compound, that is, no additional heating treatment is required during the reaction.
[0068] According to an embodiment of the present invention, in step (2), the photocatalytic coupling reaction of benzylamine compounds is carried out under an air atmosphere, that is, no additional oxygen needs to be introduced during the reaction.
[0069] According to an embodiment of the present invention, in step (2), the method for generating the ultraviolet light is not particularly limited, as long as ultraviolet light can be obtained, for example, the surface of the titanium oxide film catalytic material can be irradiated by an LED ultraviolet lamp.
[0070] According to an embodiment of the present invention, in step (2), the intensity of the ultraviolet light is 61-412 mW / cm -2 .
[0071] According to an embodiment of the present invention, in step (2), the method for generating the pressure difference is not particularly limited. For example, negative pressure may be generated on the lower surface of the titanium oxide film catalyst material by vacuum filtration, and / or positive pressure may be generated on the upper surface of the titanium oxide film catalyst material by applying external pressure.
[0072] Exemplarily, the pressure difference is achieved by vacuum filtration, for example, adding the transmembrane reaction solution to a vacuum filtration device provided with a titanium oxide film catalytic material, starting the vacuum pump, and performing vacuum filtration to generate a pressure difference between the upper and lower surfaces of the titanium oxide film catalytic material.
[0073] According to an embodiment of the present invention, in step (2), the magnitude of the pressure difference is not particularly limited, such as being greater than 0.5 atm. Exemplarily, the pressure difference is 0.5-1.0 atm, such as 0.8-1.0 atm, such as 0.5 atm, 0.6 atm, 0.7 atm, 0.8 atm, 0.9 atm or 1.0 atm.
[0074] According to an embodiment of the present invention, in step (2), the yield of the reaction is 70-100%.
[0075] Beneficial effects of the present invention:
[0076] The present invention is based on the concept of confined flow chemical reaction in an artificial system. It utilizes the intrinsic semiconductor charge separation photocatalytic properties of two-dimensional nano-element materials titanium oxide nanosheets and the synergistic catalytic effect of two-dimensional nano-confined channels provided after the two-dimensional nano-element materials are assembled into macroscopic thin films. The method reduces the molecular freedom of reactants and the disordered diffusion caused by thermal motion in the solution, reduces the activation energy of the chemical reaction, and changes the chemical reaction path, thereby achieving rapid and high-yield photocatalytic coupling of benzylamine compounds to prepare imines.
[0077] The titanium oxide film catalytic material of the present invention has semiconductor properties and can produce reactive oxygen species under ultraviolet light excitation. The titanium oxide film catalytic material has a narrow band gap, which can effectively promote charge separation. Combined with the two-dimensional nano-confined channels provided between the titanium oxide film catalytic material layers, the reactant molecules have reduced degrees of freedom, allowing the molecules to break and form bonds in a specific orientation. This ensures that the molecules pass through the confined channels in an orderly manner, reducing the reaction activation energy and changing the reaction path. Therefore, this confined catalytic mechanism based on artificial systems will significantly improve the catalytic effect of the catalyst.
[0078] The present invention regulates the interlayer spacing, active oxygen species content and reaction time of the titanium oxide film catalytic material by changing the heat treatment temperature, light intensity and film thickness, optimizes the compatibility of the confined photocatalytic benzylamine compound coupling to prepare imine reaction system and reactant molecules, and significantly improves the catalytic effect of the titanium oxide film catalytic material.
[0079] The titanium oxide film catalytic material of the present invention can be used for the rapid and high-yield photocatalytic coupling of benzylamine compounds to prepare imines. The reactants react in the two-dimensional nano-confined channels between the titanium oxide film catalytic material layers in a continuous mobile phase reaction mode. The product imine flows out with the mobile phase, achieving rapid (0.1-100s) and high-yield (70-100%) synthesis of imines and simplifying the separation and purification process. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 : A flow chart of the preparation process of the titanium oxide film catalytic material described in a preferred embodiment of the present invention.
[0081] Figure 2 : An optical photograph of the titanium oxide film catalytic material according to a preferred embodiment of the present invention.
[0082] Figure 3 : A scanning electron microscope image of the titanium oxide film catalytic material according to a preferred embodiment of the present invention.
[0083] Figure 4 : A process flow chart of the preparation of imines by photocatalytic coupling of benzylamine compounds using a titanium oxide film catalyst material as described in a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0084] The present invention will be described in further detail below with reference to specific examples. It should be understood that the following examples are merely illustrative and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are encompassed within the scope of protection that the present invention is intended to protect.
[0085] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the reagents, materials, etc. used in the following examples are all commercially available unless otherwise specified.
[0086] In the following examples and comparative examples, unless otherwise specified, “TO aqueous solution” refers to “titanium oxide nanosheet dispersion”.
[0087] In the following examples and comparative examples, unless otherwise specified, "TO film" refers to "titanium oxide film catalytic material".
[0088] In the following examples and comparative examples, unless otherwise specified, "TTO membrane" refers to "heat-treated titanium oxide membrane catalytic material".
[0089] In the following examples and comparative examples, quantitative analysis of the permeate products by gas chromatography and calculation of the reaction yields were performed. The steps specifically included the following: After the reaction, ethanol was added to a filter flask to obtain a product collection solution, and a portion of the product collection solution was transferred to a chromatographic injection vial to obtain a gas chromatography sample. Different substances have different characteristic retention times in a gas chromatograph. The peak area at this characteristic retention time corresponds to the mass of the substance, allowing the molar amount of the substance to be calculated. The reaction yield was then calculated by comparing the corresponding molar amounts.
[0090] Example 1
[0091] (1) 4.6 g of cesium carbonate (Cs2CO3) and 5.98 g of nano-titanium dioxide (TiO2) were mixed and ground, and then calcined at 800 ° C for 20 hours; the grinding and calcination were repeated twice to obtain cesium titanate (Cs 0.7 Ti1.825 O4); Place cesium titanate powder in 1 mol / L hydrochloric acid for 72 hours, and replace the hydrochloric acid every 24 hours, and filter to obtain titanic acid (H 0.7 Ti 1.825 The solid was washed with deionized water three times and then air-dried for later use.
[0092] Take 1 g of titanate solid powder and add it to 250 mL of 0.04 mol / L tetrabutylammonium hydroxide aqueous solution. After mechanical shaking for 14 days, dilute it with water to obtain a TO aqueous solution with a concentration of 2.0 mg / mL, which is stored for later use.
[0093] (2) Take 0.5 mL of the prepared TO aqueous solution and dilute it to 25 mL with deionized water. Then assemble it into a TO membrane by vacuum filtration. After the water above the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber maintained at 25°C and 15% RH for 12 hours to obtain a TO membrane. The obtained TO membrane has a thickness of 2.50 μm, a titanium to oxygen atomic ratio of 0.45, and an interlayer spacing of 1.58 nm.
[0094] (3) Using TO film as a catalyst, at 412mW / cm -2 The coupling reaction of benzylamine was catalyzed under ultraviolet light. The specific operation was as follows: the TO membrane was purged with nitrogen to remove surface dust, fixed and installed with a sealing gasket to ensure that it was sealed in the micro-filtration device; then the membrane reaction solution was prepared: 25mL of acetonitrile was added with 0.5mmol of benzylamine and mechanically stirred for 10 minutes; then 5mL of the above membrane reaction solution was added to the columnar filter cup above the filtration device. Driven by the pressure difference (~1atm), the membrane reaction solution passed through the two-dimensional nano-confined channel between the layers of the TO membrane, and 412mW / cm was applied above the TO membrane. -2 Under ultraviolet light, the reactant benzylamine undergoes a photocatalytic reaction between the layers of the TO membrane, and the product imine elutes with acetonitrile. Ethanol is added to the bottom triangular collection flask to dissolve the product. A portion of the collected liquid is transferred to a chromatographic injection vial. The composition is analyzed by gas chromatography, and the reaction yield is calculated.
[0095] Reaction results: reaction time was 6.62s and the yield was 99%.
[0096] Comparative Example 1
[0097] (1) Same as step (1) of Example 1.
[0098] (2) Take 0.5 mL of the prepared TO aqueous solution in a centrifuge tube, immerse it in liquid nitrogen and freeze it, then freeze-dry it for 48 hours to obtain TO powder, and then place it in a constant temperature and humidity chamber maintained at 25°C and 15RH% for 12 hours to obtain TO powder; then prepare the reaction solution: take 25 mL of acetonitrile, add 0.5 mmol of benzylamine, and stir mechanically for 10 minutes; take 5 mL of the above reaction solution and TO powder, add them to a glass bottle, stir mechanically for 10 minutes, and apply 412 mW / cm above the glass bottle. -2 After 6 hours of reaction, 0.1 mL of the reaction solution was sampled into a chromatographic injection vial and diluted with 0.9 mL of ethanol. The components were analyzed by gas chromatography and the reaction yield was calculated.
[0099] Reaction results: The reaction time was 6 hours and the yield was 49%.
[0100] Example 2
[0101] Other operations are the same as in Example 1, except that:
[0102] The TO film was placed in a constant temperature and humidity chamber at 25°C and 15 RH% for 12 hours in step (2) and then transferred to an oven for heat treatment at 40°C for 12 hours to obtain a TTO film. The interlayer spacing of the obtained TTO film was 1.51 nm. The TTO film was used as a catalyst at 310 mW / cm -2 The coupling reaction of benzylamine was catalyzed under ultraviolet light irradiation, and the specific process is shown in Example 1. Reaction results: reaction time was 5.79 s, and the yield was 81%.
[0103] Example 3-1
[0104] Other operations are the same as in Example 1, except that:
[0105] (2) Take 0.42 mL of the prepared TO aqueous solution and dilute it to 25 mL with deionized water. Then assemble it into a TO membrane by vacuum filtration. After the water above the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber at 25°C and 15RH% for 12 hours.
[0106] (3) The thickness of the obtained TO film is 2.08 μm, the atomic ratio of titanium to oxygen is 0.45, and the interlayer distance is 1.58 nm. The TO film is used as a catalyst and the -2 Benzylamine was catalyzed to undergo a coupling reaction under ultraviolet light irradiation, and the specific process was as shown in Example 1.
[0107] Reaction results: reaction time was 5.79s and the yield was 98%.
[0108] Example 3-2
[0109] Other operations are the same as in Example 1, except that:
[0110] (2) Take 0.33 mL of the prepared TO aqueous solution and dilute it to 25 mL with deionized water. Then assemble it into a TO membrane by vacuum filtration. After the water above the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber at 25°C and 15RH% for 12 hours.
[0111] (3) The thickness of the obtained TO film is 1.67 μm, the atomic ratio of titanium to oxygen is 0.45, and the interlayer distance is 1.58 nm. The TO film is used as a catalyst and the -2 Benzylamine was catalyzed to undergo a coupling reaction under ultraviolet light irradiation, and the specific process was as shown in Example 1.
[0112] Reaction results: reaction time was 3.09s and the yield was 95%.
[0113] Example 3-3
[0114] Other operations are the same as in Example 1, except that:
[0115] (2) Take 0.25 mL of the prepared TO aqueous solution and dilute it to 25 mL with deionized water. Then assemble it into a TO membrane by vacuum filtration. After the water above the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber at 25°C and 15RH% for 12 hours.
[0116] (3) The thickness of the obtained TO film is 1.25 μm, the atomic ratio of titanium to oxygen is 0.45, and the interlayer spacing is 1.58 nm. The TO film is used as a catalyst and the -2 Benzylamine was catalyzed to undergo a coupling reaction under ultraviolet light irradiation, and the specific process was as shown in Example 1.
[0117] Reaction results: reaction time was 1.63s and the yield was 83%.
[0118] Examples 3-4
[0119] Other operations are the same as in Example 1, except that:
[0120] (2) Take 0.17 mL of the prepared TO aqueous solution and dilute it to 25 mL with deionized water. Then assemble it into a TO membrane by vacuum filtration. After the water above the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber maintained at 25°C and 15RH% for 12 hours.
[0121] (3) The thickness of the obtained TO film is 0.83 μm, the atomic ratio of titanium to oxygen is 0.45, and the interlayer distance is 1.58 nm. The TO film is used as a catalyst and the -2 Benzylamine was catalyzed to undergo a coupling reaction under ultraviolet light irradiation, and the specific process was as shown in Example 1.
[0122] Reaction results: reaction time was 1.39s and the yield was 75%.
[0123] Example 4-1
[0124] Other operations are the same as in Example 1, except that:
[0125] Using TO film as a catalyst, at 412mW / cm -2 The coupling reaction of 4-methylbenzylamine was catalyzed under ultraviolet light.
[0126] Reaction results: reaction time was 6.77s and the yield was 98%.
[0127] Example 4-2
[0128] Other operations are the same as in Example 1, except that:
[0129] Using TO film as a catalyst, at 412mW / cm -2 The coupling reaction of 3-methylbenzylamine was catalyzed under ultraviolet light.
[0130] Reaction results: reaction time was 6.62s and the yield was 98%.
[0131] Example 4-3
[0132] Other operations are the same as in Example 1, except that:
[0133] Using TO film as a catalyst, at 412mW / cm -2 The coupling reaction was catalyzed by 4-chlorobenzylamine under ultraviolet light irradiation.
[0134] Reaction results: reaction time was 4.79s and the yield was 96%.
[0135] Example 4-4
[0136] Other operations are the same as in Example 1, except that:
[0137] Using TO film as a catalyst, the -2 The coupling reaction was catalyzed by 3-chlorobenzylamine under ultraviolet light irradiation.
[0138] Reaction results: reaction time was 6.26s and the yield was 97%.
[0139] Examples 4-5
[0140] Other operations are the same as in Example 1, except that:
[0141] Using TO film as a catalyst, the -2 The coupling reaction of 4-methoxybenzylamine was catalyzed under ultraviolet light.
[0142] Reaction results: reaction time was 8.34s and the yield was 98%.
[0143] Examples 4-6
[0144] Other operations are the same as in Example 1, except that:
[0145] Using TO film as a catalyst, the -2 The coupling reaction was catalyzed by 4-bromobenzylamine under ultraviolet light.
[0146] Reaction results: reaction time was 7.42s and the yield was 98%.
[0147] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included in the scope of protection of the present invention.
Claims
1. A titanium oxide film catalytic material for photocatalytic coupling of benzylamine compounds to prepare imines, characterized in that: The interlayer spacing of the titanium oxide film catalyst material is 1.40nm-1.60nm, and the atomic ratio of titanium to oxygen in the titanium oxide film catalyst material is 0.440-0.465; The titanium oxide film catalytic material is prepared by assembling titanium oxide nanosheets by vacuum filtration; the thickness of the titanium oxide nanosheets is 1.0nm-1.5nm; the chemical formula of the titanium oxide nanosheets is Ti y O2, 0.93≥y≥0.
88.
2. The titanium oxide film catalytic material according to claim 1, characterized in that: The thickness of the titanium oxide film catalytic material is 0.5-10 μm.
3. The method for preparing the titanium oxide film catalyst material according to claim 1 or 2, the method comprising the following steps: (1) titanium dioxide and cesium carbonate are mixed and calcined to prepare layered cesium titanate; the layered cesium titanate is mixed with an acid and subjected to a protonation reaction to prepare titanic acid; (2) adding titanic acid to an aqueous solution of tetrabutylammonium hydroxide to carry out an exfoliation reaction to prepare titanium oxide nanosheets; (3) Assembling titanium oxide nanosheets into titanium oxide membranes by vacuum filtration to obtain the titanium oxide membrane catalytic material.
4. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of titanium dioxide to cesium carbonate is 1:0.5-3; And / or, in step (1), the calcination temperature is 600-1000°C; the calcination time is 10-40 hours; And / or, in step (1), the chemical formula of the cesium titanate is Cs x Ti 2-x / 4 O4, 0.6 <x≤1.0; And / or, in step (1), the chemical formula of the titanic acid is H x Ti 2-x / 4 O4, 0.6 <x≤1.0; And / or, in step (2), the mass molar ratio of titanic acid to tetrabutylammonium hydroxide is 0.05-1 g / mmol.
5. The preparation method according to claim 3 or 4, characterized in that: The method further comprises the steps of: (4) Heat treating the titanium oxide film catalyst material of step (3).
6. The preparation method according to claim 5, characterized in that: In step (4), the heat treatment time is 8-16 hours; the heat treatment temperature is 40-120°C.
7. The titanium oxide film catalytic material prepared by the method according to any one of claims 3 to 6.
8. Use of the titanium oxide film catalytic material according to any one of claims 1 to 2 and 7 for photocatalytic coupling of benzylamine compounds to prepare imines.
9. A method for preparing imines by photocatalytic coupling of benzylamine compounds, the method comprising the following steps: (1) dissolving a benzylamine compound in an organic solvent to obtain a membrane reaction solution; (2) The cross-membrane reaction solution is driven by pressure difference and subjected to ultraviolet light to pass through the titanium oxide film catalytic material according to any one of claims 1 to 2 and 7 to perform a photocatalytic coupling reaction of benzylamine compounds.
10. The method according to claim 9, characterized in that In step (1), the concentration of the benzylamine compound in the transmembrane reaction solution is 0.01-5 mol / L; and / or, in step (1), the benzylamine compound is selected from at least one of benzylamine, 2-methylbenzylamine, 3-methylbenzylamine, 4-methylbenzylamine, 2-trifluoromethylbenzylamine, 3-trifluoromethylbenzylamine, 4-trifluoromethylbenzylamine, 2-methoxybenzylamine, 3-methoxybenzylamine, 4-methoxybenzylamine, 2-tert-butylbenzylamine, 3-tert-butylbenzylamine, 4-tert-butylbenzylamine, 2,3-difluorobenzylamine, 2,4-difluorobenzylamine, 2,3-dichlorobenzylamine, 2,4-dichlorobenzylamine, 2,3-dibromobenzylamine, 2,4-dibromobenzylamine, 2-fluorobenzylamine, 3-fluorobenzylamine, 4-fluorobenzylamine, 2-chlorobenzylamine, 3-chlorobenzylamine, 4-chlorobenzylamine, 2-bromobenzylamine, 3-bromobenzylamine and 4-bromobenzylamine; And / or, in step (2), the reaction time of the photocatalytic coupling reaction of the benzylamine compound is 0.1-100 s; And / or, in step (2), the pressure difference is 0.5-1.0 atm.
Citation Information
Patent Citations
Ultrathin two-dimensional titanium oxide nanosheet material with large specific surface and preparing method
CN109133162A
Preparation and application of mineral functional membrane coupled with advanced oxidation technology
CN117323842A